2016
DOI: 10.1017/s0033291716001070
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of eye movement desensitization and reprocessing for post-traumatic stress disorder and depression among Syrian refugees: results of a randomized controlled trial

Abstract: EMDR may be effective in reducing PTSD and depression symptoms among Syrian refugees with PTSD located in a refugee camp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
122
1
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(133 citation statements)
references
References 35 publications
3
122
1
7
Order By: Relevance
“…The statistically significant reduction in subjective stress ratings following treatment with BLAST agrees with a previous study by our group showing significant reductions in subjective ratings of both physical and psychological stress following 30 seconds of treatment with BLAST as compared to their baseline[18]. It also supports several studies which have shown a beneficial effect of EMDR-based treatment on patients with high levels of anxiety[13,15,27]. The significant reduction in salivary cortisol levels in the treatment group as compared to the control group also is consistent with these results but, as a more quantitative and objective metric of the stress response[22], provides a novel and compelling additional support for the benefit of BLAST in attenuating the stress response.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…The statistically significant reduction in subjective stress ratings following treatment with BLAST agrees with a previous study by our group showing significant reductions in subjective ratings of both physical and psychological stress following 30 seconds of treatment with BLAST as compared to their baseline[18]. It also supports several studies which have shown a beneficial effect of EMDR-based treatment on patients with high levels of anxiety[13,15,27]. The significant reduction in salivary cortisol levels in the treatment group as compared to the control group also is consistent with these results but, as a more quantitative and objective metric of the stress response[22], provides a novel and compelling additional support for the benefit of BLAST in attenuating the stress response.…”
supporting
confidence: 90%
“…Several clinical trials have also shown positive effects of EMDR in adults with autism spectrum disorder [12], depression [13,14], and post-traumatic stress disorder [15,16]. • male (to avoid the effect of menstrual cycle and oral contraceptive use on cortisol levels),…”
Section: Introductionmentioning
confidence: 99%
“…Seventeen of the trials assessed PTSD and 13 trials assessed depression. Of the 12 trials assessing symptoms of both PTSD and depression, seven trials had focused on both PTSD and depression (Acarturk et al., ; Acarturk et al., ; Bass et al., ; Bass et al., ; Bolton et al., ; Meffert et al., ; Weiss et al., ), four reported treatment of PTSD as the major focus and additionally measured the efficacy of the intervention for depression among individuals with PTSD (Bryant et al., ; Connolly & Sakai, ; Hagl, Powell, Rosner, & Butollo, ; Knaevelsrud, Brand, Lange, Ruwaard, & Wagner, ), and one reported treatment of depression as the main focus and assessed symptoms of PTSD as secondary outcome (Bolton et al., ). Five trials assessed PTSD only (Igreja, Kleijn, Schreuder, Van Dijk, & Verschuur, ; Jacob, Neuner, Maedl, Schaal, & Elbert, ; Neuner et al., ; Neuner, Schauer, Klaschik, Karunakara, & Elbert, ; Yeomans, Forman, Herbert, & Yuen, ), whereas one trial assessed depression only (Bolton et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Two small RCTs in Syrian refugees located in Kilis refugee camp in Turkey evaluated the efficacy of EMDR for PTSD (Acarturk et al, 2015, 2016). These studies showed that both symptoms of PTSD and depression significantly reduced in refugees who received EMDR (Acarturk et al, 2015, 2016). …”
Section: Evidence-based Interventions For Refugeesmentioning
confidence: 99%